2019
DOI: 10.1108/ajim-09-2018-0212
|View full text |Cite
|
Sign up to set email alerts
|

User adoption of a hybrid social tagging approach in an online knowledge community

Abstract: Purpose Online knowledge communities make great contributions to global knowledge sharing and innovation. Resource tagging approaches have been widely adopted in such communities to describe, annotate and organize knowledge resources mainly through users’ participation. However, it is unclear what causes the adoption of a particular resource tagging approach. The purpose of this paper is to identify factors that drive users to use a hybrid social tagging approach. Design/methodology/approach Technology accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…This finding concurs with prior work (e.g. Naranjo-Zolotov et al , 2019; Qin et al , 2019), and is especially pertinent in the case of Zhongxun because of the nature of the crowdsourced task. That is, users have to capture photos of children they suspect to be trafficked.…”
Section: Discussionsupporting
confidence: 90%
“…This finding concurs with prior work (e.g. Naranjo-Zolotov et al , 2019; Qin et al , 2019), and is especially pertinent in the case of Zhongxun because of the nature of the crowdsourced task. That is, users have to capture photos of children they suspect to be trafficked.…”
Section: Discussionsupporting
confidence: 90%
“…Previous literature regarding information sharing on social media, primarily relied on users' motivation and their attitude, towards well-known social media platforms such as Facebook and Ren-Ren (a Chinese social media platform) -covering only specific countries (Chang & Zhu, 2011;Chu et al, 2011;Lien & Cao, 2014;Lien et al, 2017). In addition, individual's motivational factors are considered as driving forces to influence information sharing behavior via social media platforms (Tan & Lee, 2019;Qin et al, 2019). Furthermore, at network level, timeliness of information, technology readiness, information sufficiency, perceived complexity, perceived complementary and perceived richness are important network factors which may potentially affect users' information sharing behavior (Shang et al, 2017;Chang, 2018;Chen et al, 2018;Sullivan & Koh, 2019).…”
Section: Related Studiesmentioning
confidence: 99%
“…While the technology used to share online information -internet connectivity or Wi-Fi has been common, few studies found that information sharing through electronic media will be affected by sufficient technical expertise (Kim et al, 2015;Qin et al, 2019). Some scholars have suggested that users' experience about different social media features will positively affect their intentions to share e-content and information via social media platforms (Kim et al, 2015).…”
Section: Past Sharing Experiencementioning
confidence: 99%
See 2 more Smart Citations